Closed-Aperture Z-Scan Analysis for Nonlinear Media with Saturable Absorption and Simultaneous Third- and Fifth-Order Nonlinear Refraction. (7th August 2012) - Liu, Xiangming; Tomita, Yasuo
Abstract : We present a theory of open- and closed-aperture Gaussian beam Z-scan for nonlinear optical materials with saturable absorption and high-order nonlinear refraction. We show that an approximate expression for a transmitted intensity through the nonlinear optical material is possible by means of the Adomian's decomposition method and the thin film approximation. The theory is applied to semiconductor CdSe quantum dot-polymer nanocomposite films. It is shown that the theory well explains measured results of open- and closed-aperture transmittances in the Z-scan setup. It is also shown that the nanocomposite film possesses simultaneous third- and fifth-order nonlinear refraction as well as saturable absorption of a homogeneously broadened type.